Anatomy of the Naviculocuneiform Joint. Issue 1 (January 2022) - Borrelli, George J.; Qatu, Mossub; Traynor, Christopher J.; Weistroffer, Joseph; Jastifer, James R.
Category: Midfoot/Forefoot; Basic Sciences/Biologics Introduction/Purpose: The naviculocuneiform (NC) joint has a role in numerous pathologies of the foot and ankle. There is little in the published literature quantifying the cartilage of the articulating surface and its unique anatomical features. The purpose of this study was to quantify and describe the articular surface of the NC joint. Our hypothesis was that the cartilage surface would have anatomic features that would guide surgeons when performing procedures such as joint preparation and screw placement. Methods: Twenty cadaver NC joints were dissected, and the articular cartilage quantified by calibrated digital imaging software. Results: The mean dorsal to plantar height of the navicular facets was 18mm, with a maximum height not exceeding 21mm. The mean height of the medial, middle, and lateral cuneiform facets was 15mm, 17mm, and 15mm, respectively. The mean length from the medial to middle navicular facet was 14mm, approximately 41.3% the mean length across all three navicular facets (34mm). For the distal navicular articulation, 75.4% of the mean surface area was articular cartilage. For the proximal medial, middle, and lateral cuneiform articulations, 69.6%, 75.7%, and 75.8% of the mean surface areas were articular cartilage, respectively. Conclusion: This study provides an anatomic description of the NC joint to guide surgeons when operating on the NC joint. Two clinical observations can be made from this data. First, when preparing the NC joint for arthrodesis from a dorsal approach, the surgeon should be aware that the cartilage of the NC joint can extend up to 21mm from dorsal to plantar. This is also a useful estimate of screw length in the subchondral bone. Second, the central third of the navicular, where the majority of navicular stress fractures occur, lies in the inter-facet ridge between the medial and middle facets.